Evaluation of the possibility of application of the Attenuated Total Reflectance spectroscopy (ATR-FTIR) in compatibility studies of metformin hydrochloride with selected excipients - Joanna Ronowicz; Agnieszka Płóciennik (Polish Pharmaceutical Society, 2020)
The compatibility assessment of formulation ingredients is one of the key stages of research and development work on a new medicinal product. The submission of the results of chemical interaction studies is required in the registration dossier. Nevertheless, there are no clearly defined guidelines regarding the method of sample preparation and conditions for testing the compatibility of pharmaceutical raw materials. The aim of the study was to assess the usefulness of the Attenuated Total Reflectance spectroscopy (ATR-FTIR) in the evaluation of chemical interactions of metformin hydrochloride with selected excipients in the solid phase. The use of the ATR-FTIR technique was considered due to its non-invasive nature, no need for special sample preparation, short time needed to register the infrared spectrum and a small amount of sample needed to perform the test. The tested samples were two-component, equilibrium (1: 1, w/w) mixtures of the active substance with the appropriate excipient (potato starch, ultraamylopectin, magnesium stearate, Methocel E15). In order to assess possible chemical interactions, spectroscopic tests were performed immediately after the mixtures were prepared and after their 3-month exposure to the temperature of 50°C and 50% RH humidity in a climatic chamber. ATR-FTIR spectra were recorded in the wavenumber range from 4000 cm-1 to 600 cm-1, with a resolution of 4 cm-1. The detected changes in the ATR-FTIR spectra (such as absorption bands shifts, modifications in shape and intensity of bands, disappearance or appearance of additional absorption bands) indicated possible changes in the chemical structure of metformin hydrochloride and thus a chemical interaction with tested excipients. The research studies confirmed that the non-invasive and non-destructive ATR-FTIR technique can be valuable initial screening method in the physicochemical compatibility studies of metformin hydrochloride at the stage of defining the qualitative composition of the pharmaceutical formulation. However, full compatibility analysis of the pharmaceutical formulation ingredients requires the use of complementary techniques that verify the presence of changes in the chemical structure of the active substance.